Introduction and Content of Forest Regulation (1861) - Stanković, Uroš (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
The article sheds light on introduction and content of Forest Regulation (1861). The idea of producing new Forest Regulation which would replace the existing act regulating same matter, introduced in 1857, came out as a result of people’s discontent with limited opportunities for wood-cutting. The Committee for requests and proposals of so-called Saint Andrew’s Day Assembly (1858), on which prince Alexander Karađorđević (1842–1858) had been dethroned and ex-prince Miloš Obrenović (1815–1839) reinstated to the throne, designed directives on which new forest legislation should have been based. Relying on these directives, in 1859 an unknown author made a Draft Forest Regulation consisting of 43 articles. In January 1861, the Draft was revised and supplemented by a three-membered committee formed by the State Council in the very end of 1860. The Council slightly altered the revised draft. Prince Mihailo Obrenović approved the text and it was enacted as Forest Regulation in 1861. In comparison with previous Forest Regulation, the act passed in 1861 was more liberal towards wood-cutting. Taxes on wood-cutting for economic purpose were lowered. Instead of Ministry of finances, district office was now competent to approve cutting wood for fodder. As a local authority, much more familiar with its fellow-inhabitants, district office was more likely to fulfill their exaggered wishes to destroy woods for above-mentioned purpose. The scope of population having right to be awarded piece of land with forest in order to broaden their insuficient landed property was widened. The reason for this step-back in forest protection in Serbia was obvious. New dinasty had to present itself as better than precedent government. At that moment nobody was aware of high toll to be payed for extensive destruction of forests.